Go, a guanine nucleotide-binding protein: immunohistochemical localization in rat brain resembles distribution of second messenger systems. - Worley, P F (1986)
We have localized a guanine nucleotide-binding protein, Go, in rat brain by immunohistochemistry with a selective polyclonal antiserum to the alpha 39 subunit of Go. Specific staining is widely distributed, abundant in neuropil, absent from neuronal cell bodies, and displays regional heterogeneity. Staining is enriched in cerebral cortex, particularly the molecular layer, neuropil of the hippocampal formation, striatum, substantia nigra pars reticulata, molecular layer of the cerebellum, substantia gelatinosa of the spinal cord, and posterior pituitary. High density staining in the substantia nigra reflects a Go-containing striatonigral pathway since striatal lesions reduce ipsilateral immunostaining in the pars reticulata. Confirming immunostaining, quantitative [32P]ADP-ribosylation of nigral membranes with pertussis toxin indicates a 66% +/- 11% (mean +/- SEM) reduction of Go ipsilateral to striatal lesions. Go may be associated with Purkinje cells in the cerebellum since membranes from mutant mice (Nervous), which postnatally lose Purkinje cells, are markedly depleted in pertussis toxin substrate. The localizations of Go correspond in many areas with those of protein kinase C, a component of the phosphatidylinositol cycle, suggesting a major role for Go in the brain related to regulation of the phosphatidylinositol cycle.